2020
DOI: 10.1186/s42077-020-0053-7
|View full text |Cite
|
Sign up to set email alerts
|

Erector spinae plane block in laparoscopic cholecystectomy: a case report

Abstract: Background Ultrasound-guided erector spinae plane block has been reported to reduce postoperative pain following a laparoscopic surgery, which is one of the most common abdominal surgeries. The case reports and randomized controlled trials published previously mostly used bilateral erector spinae plane block; however, we report a case in which a unilateral erector spinae plane block was performed. Case presentation A 34-year-old male patient who underwent laparoscopic cholecystectomy was scheduled for a unila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…QLB was carried out with the case lying on both sides. A high-frequency linear array US probe is used following local povidone iodine sterilization (5)(6)(7)(8)(9)(10)(11)(12)(13). Above the iliac crest, a clean sheath was positioned.…”
Section: Technique Of Ultrasound Guided Quadratus Lumborum Block (Typ...mentioning
confidence: 99%
“…QLB was carried out with the case lying on both sides. A high-frequency linear array US probe is used following local povidone iodine sterilization (5)(6)(7)(8)(9)(10)(11)(12)(13). Above the iliac crest, a clean sheath was positioned.…”
Section: Technique Of Ultrasound Guided Quadratus Lumborum Block (Typ...mentioning
confidence: 99%
“…Bilateral ESPB has been compared to STAP with similar or superior analgesia after LC (29)(30)(31). Case reports (4,32,33) and randomized control trials (34)(35)(36)(37)(38) have shown the efficacy of bilateral ESPB for pain control after LC, though the effects of unilateral ESPB have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%